Development of an in vivo radiographic method with potential for use in improving bone quality and the welfare of laying hens through genetic selection. Issue 1 (2nd January 2023) - Wilson, P. W.; Dunn, I. C.; Mccormack, H. A.
ABSTRACT: 1. Genetic selection for bone quality can improve this, as it is heritable. A method was established using digital X-ray which took around 40 s in total and gave an image that allowed quantification of bone density from many appendicular bones. 2. The tibiotarsus measurement of bone density on the live hen across the different experiments had correlations with post-mortem whole bone radiographic density from 0.62 to 0.7, similar to that between density and material properties for example. Differences between groups of hens, where calcium and phosphorus in the diet were manipulated, were detected within 3 weeks of treatment using live hen measurement (P < 0.001, n = 24). 3. In a gage analysis, 'hen' explained more than 86% of the variance, demonstrating the ability to observe clear differences between hens. The effect of different operators' analysis on the contribution to variance was very low as was the repeated measurement of the same hen. 4. The measurement of bone density on the live hen described in this paper represented major progress to a usable method for genetic selection to improve bone strength in laying hens. The method has the potential to reduce the number of animals needed to test nutritional and management interventions to improve bone health.